GENDER APPROACH TO PREVENTING WOMEN'S INVOLVEMENT IN TERRORISM IN INDONESIA - Rifkah Nurullita (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
In recent years, there has been an increase in women's involvement in terrorism in Indonesia. The evolution of women involved in terrorism is not only limited to followers, but has increased and become more dangerous. Extremist groups use women in their acts of terror because they see an opportunity for women to become suicide perpetrators. Gender gaps and inequality are factors for women to be involved in the action. How patriarchal views and masculinity constructs affect radicalization and acts of violent extremism, so a gender-based approach is needed to be able to promote gender equality and mitigate discrimination, and can be actualized in terrorism prevention strategies in Indonesia.